2020
DOI: 10.1038/s41598-020-69911-1
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering unique plasticity in life history of an endangered centenarian fish

Abstract: The ability to adapt to changing environments is fundamental for species persistence. Both plasticity and genetic selection are potential drivers that allow for traits to be advantageous, thus leading to increases in survival or fitness. Identifying phenotypic plasticity in life history traits of long-lived organisms can be difficult owing to high survival, long generation times, and few studies at sufficient spatial and temporal scales to elicit a plastic response within a population. To begin to understand p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Note that reproductive failure during the first reproductive cycle has not been examined in the lower Missouri River and could be a priority for future research. Pallid sturgeon above Fort Peck Reservoir becoming reproductively mature at older ages and larger sizes than other locations is explained by recent research, which found that phenotypic plasticity allows pallid sturgeon in the upper Missouri River to grow slower but grow larger and reach maturity at older ages than pallid sturgeon in other locations (Hamel et al, 2020). Furthermore, the pallid sturgeon population above Fort Peck Reservoir is at the northern periphery of the range of pallid sturgeon and becoming reproductively mature at older ages and larger sizes than more southerly populations may be related to geographic latitude, which has been described in other species such as Atlantic Cod ( Gadus morhua ; Thorsen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that reproductive failure during the first reproductive cycle has not been examined in the lower Missouri River and could be a priority for future research. Pallid sturgeon above Fort Peck Reservoir becoming reproductively mature at older ages and larger sizes than other locations is explained by recent research, which found that phenotypic plasticity allows pallid sturgeon in the upper Missouri River to grow slower but grow larger and reach maturity at older ages than pallid sturgeon in other locations (Hamel et al, 2020). Furthermore, the pallid sturgeon population above Fort Peck Reservoir is at the northern periphery of the range of pallid sturgeon and becoming reproductively mature at older ages and larger sizes than more southerly populations may be related to geographic latitude, which has been described in other species such as Atlantic Cod ( Gadus morhua ; Thorsen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, reproductive hatchery-origin female and male pallid sturgeon from 9-14 years old were documented in the lower Missouri River(DeLonay et al, 2009), and we documented spawning-capable male and female pallid sturgeon varying from 15 to 22 years old in the Missouri River above Fort Peck Reservoir. Note that reproductive failure during the first reproductive cycle has not been examined in the lower Missouri River and could be a priority for future research.Pallid sturgeon above Fort Peck Reservoir becoming reproductively mature at older ages and larger sizes than other locations is explained by recent research, which found that phenotypic plasticity allows pallid sturgeon in the upper Missouri River to grow slower but grow larger and reach maturity at older ages than pallid sturgeon in other locations(Hamel et al, 2020). Furthermore, the pallid sturgeon population above Fort Peck Reservoir is at the northern periphery of the range of pallid sturgeon and becoming reproductively mature at older ages and larger sizes than more southerly populations may be related to geographic latitude, which has been described in other species such as Atlantic Cod (Gadus morhua;Thorsen et al, 2010).Massovarian follicular atresia was experienced by all hatcheryorigin female pallid sturgeon observed during their first reproductive cycles, half of those observed during presumed-first reproductive cycles, and one third of those observed during subsequent reproductive cycles.…”
mentioning
confidence: 99%
“…This is particularly true when reintroducing extirpated populations to modified systems via hatchery augmentation because the reproductive ecology of wild fish in these systems is often unknown and the relative reproductive success of stocked individuals can be difficult to gauge. Because lifehistory traits in periodic fishes can also be plastic (Hamel et al, 2020), we suggest that it may be important to quantify traits of interest in situ, rather than under hatchery settings that may not adequately reflect resource availability or other stressors in the wild. Moreover, because recruitment success of periodic strategists is often related to density-independent environmental factors over large spatiotemporal scales (Winemiller & Dailey, 2002), identifying life-stage-specific bottlenecks to self-sustaining populations can be challenging (Koehn et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the fish gut analyses indicated a low incidence of empty guts, suggesting the fish species were enjoying sufficient prey/forage upon which to feed. This can be attributed to the abundant food items in the water column as illustrated by analysis of the fishes’ extensive diets, noting that diet plasticity, as shown by most fish species, is an advantage for their survival (Hamel et al, 2020). The feeding habits of fish constitute an active research area, not only for those seeking to better understand the interrelationships among or within species, but also for fishery managers who might be concerned with factors affecting a given fishery.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the fish gut analyses indicated a low incidence of empty guts, suggesting the fish species were enjoying sufficient prey/forage upon which to feed. This can be attributed to the abundant food items in the water column as illustrated by analysis of the fishes' extensive diets, noting that diet plasticity, as shown by most fish species, is an advantage for their survival (Hamel et al, 2020).…”
Section: Notable Inmentioning
confidence: 99%